Assessment of the Academic Motivation Level of Freshmen Education Students - Casinillo, Joshua (Journal of Interdisciplinary Perspectives, 2025)
Academic motivation plays an essential role in any educational setting. Analysis of students' motivation may impact students’ academic success. At VSU-Isabel, it is observed that some students have poor academic achievement, a few intend to drop out, and absenteeism is also noted. These are the severe outcomes resulting from a lack of motivation. This study employed a descriptive research design to examine the academic motivation levels of 154 university students grouped by academic program, sex, age, and scholarship status. A standardized academic motivation scale consisting of 28 items, with four items per subscale, was assessed on a 7-point scale. Results showed that BPEd students demonstrated better motivation than students in other courses. Females were more motivated than men, and students aged 20 years and above were more motivated compared to younger students. Additionally, students without scholarships showed higher motivation. It is concluded that there are no differences in the level of academic motivation across all variables involved, indicating that students have the same level of academic motivation. Theoretically, the findings reinforce the tenets of Self-Determination Theory, suggesting that autonomy and internal drivers influence motivations. Practically, the results imply the need for educational institutions to design personalized pedagogies and develop multiple instructional activities or interventions that help improve the level of academic motivation, supporting the autonomy, competence, and relatedness of these students until they successfully graduate.